APPLICATION OF HIERARCHY ANALYSIS METHOD FOR SELECTING THE PLACE OF ENTERPRISE RELOCATION (INNOVATIVE ECONOMY, 2022)
Aliluiko A.M., Yeromenko V.O., Babii C.V. APPLICATION OF HIERARCHY ANALYSIS METHOD FOR SELECTING THE PLACE OF ENTERPRISE RELOCATIONPurpose. The aim of the article is to study the possibility of using the method of analysis of hierarchies for making managerial decisions regarding the relocation of enterprises during the martial law in Ukraine.Methodology of research. Methods of general scientific and empirical techniques based on a systemic approach were used in the process of research. In addition, the following methods of scientific knowledge were used to solve the tasks: methods of analysis and observation were used to group the main factors influencing decision-making, the method of evaluations for processing expert information, the method of analysing hierarchies for solving planning and decision-making problems.Findings. The state of implementation of the Relocation Program, which was introduced by the Cabinet of Ministers of Ukraine, was studied. Criteria have been formed that can be taken into account by the management of enterprises when choosing a region of relocation from the war zone. Using the method of analysing hierarchies based on the data of expert evaluations among specialists of IT companies, it was established that such companies prefer to relocate to the westernmost regions of Ukraine, which are relatively safe and characterized by significant financial and economic support from the regional authorities. The need to introduce new organizational and economic methods of management activity in the field of enterprise accommodation is substantiated.Originality. The application of the method of analysis of hierarchies is proposed for the study of the multi-criteria management problem in the field of enterprise placement in the context of their relocation under martial law. A set of criteria that can be taken into account when making decisions regarding the choice of the place of relocation of enterprises is proposed.Practical value. The obtained results of the study are the basis for improving the organizational and economic mechanisms of management activity in the field of enterprise accommodation.Key words: hierarchy analysis method, decision-making methods, relocation of the enterprise, relocation.
Keywords: hierarchy analysis method; decision-making methods; relocation of the enterprise; relocation.